Coating composition with anti-electrostatic discharge protection and coating system comprising same
By adding aspartic acid esters, carbon nanotubes and aliphatic polyisocyanates to the aspartic acid resin system to form an antistatic coating composition, the problems of unstable performance and poor weather resistance of the existing aspartic acid resin system in antistatic coatings are solved, and excellent weather resistance and antistatic properties are achieved.
Patent Information
- Application Number
- CN202280098234.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-27
- Publication Date
- 2025-03-07
AI Technical Summary
The application of existing aspartic acid resin systems in antistatic coatings has problems of unstable performance and poor weather resistance, especially under low temperature conditions and insufficient resistance to acid and alkali.
An antistatic coating composition comprising aspartate, carbon nanotube and aliphatic polyisocyanate having at least two secondary amine groups is used to form a coating with excellent weather resistance and antistatic properties through a specific ratio and combination of additives.
It achieves stable curing under low temperature conditions, improves the weather resistance and anti-static properties of the coating, and ensures the stability of the resistance and acid and alkali resistance.
Smart Images

Figure CN119585371A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a coating composition with anti-static discharge protection and a preparation method thereof, and to a coating system for anti-static discharge protection comprising the coating composition, in particular to a floor coating system. Prior art
[0002] In many areas of industry today, the demands on optimal environmental conditions are high. In particular, avoiding uncontrolled electrostatic charging and discharging is of utmost importance.
[0003] Static electricity charging and discharging occurs as a result of contact, friction or separation of two materials. When this happens, one material becomes positively charged and the other negatively charged. In the case of floor coatings, this charge is created by walking or driving on them, for example with rubber soles or rubber tires. Air currents can also create a charge on insulating surfaces, such as paint or coatings.
[0004] In order to avoid uncontrolled electrostatic charging and discharging, conductive floor coverings with a defined electrical resistance are generally required. Floor coverings made of synthetic resins are generally non-conductive. However, by modifying the synthetic resins, for example by adding conductive pigments, ionic liquids or conductive fibers or a combination of the above examples, it is possible to produce synthetic resin coatings with precisely defined dissipation values or insulating properties. Synthetic resin coatings that have been made dissipative have therefore become widely established as defined dissipative floor coatings.
[0005] The synthetic resin coatings widely used in the modern dissipative floor coating industry are based on epoxy resin systems. However, such epoxy resin systems have poor weather resistance. In particular, the system has poor curing below 10°C, poor acid resistance, and poor scratch resistance.
[0006] In recent years, aspartic acid resin systems have attracted widespread attention due to their advantages of low-temperature curing, fast curing speed, good hardness, good adhesion to substrates, good toughness and good weather resistance, especially aspartic acid resins prepared by the reaction of low-activity secondary amines with aliphatic isocyanate curing agents. Compared with traditional aspartic acid resins prepared by the reaction of primary amines with aromatic isocyanate curing agents, aspartic acid resins prepared by the reaction of low-activity secondary amines with aliphatic isocyanate curing agents have long gel time, simple construction, fast construction speed, relatively low requirements for equipment, greatly improved coating performance, and greatly improved poor apparent adhesion, poor adhesion and poor weather resistance.
[0007] Therefore, there are many reports on the application of aspartic acid resin systems in waterproof coatings and anti-corrosion coatings, but few reports on antistatic coatings.
[0008] CN106867377A describes a self-leveling coating based on an aspartic acid resin system, but never mentions any information about antistatic properties.
[0009] CN106675485A describes a self-leveling antistatic floor coating based on an aspartic acid resin system, but the system still has problems. In addition, usually, when the resistance reaches about 10 8 Ω, it is unstable and tends to approach or reach about 10 9 Ω, even more than 10 9 Ω. In this case, the system will fail due to insulation.
[0010] Therefore, there has been a need for an antistatic coating composition based on an aspartic acid resin system having more excellent properties, such as excellent weather resistance and excellent antistatic properties. SUMMARY OF THE INVENTION
[0012] The present invention relates to an antistatic coating composition, characterized in that it comprises the following components:
[0013] Component A, one or more aspartic acid esters having at least two secondary amine groups, in an amount of 15% to 45% by weight, preferably 25% to 35% by weight, more preferably 30% to 35% by weight, based on the total amount of the composition:
[0014] Component B, carbon nanotubes, in an amount of 0.005 to 0.05 wt %, preferably 0.008 to 0.05 wt %, more preferably 0.01 to 0.02 wt %, based on the total amount of the composition: and
[0015] Component C, one or more other additives selected from dispersants, defoamers, leveling agents, anti-settling agents, adhesion promoters, water removers, inorganic powders and inactive diluents; and
[0016] Component D, at least one aliphatic polyisocyanate.
[0017] The present invention relates to a method for preparing an antistatic coating composition according to the present invention, which comprises the following steps:
[0018] a) preparing a first component by mixing in any order one or more aspartic acid esters, carbon nanotubes and one or more other additives selected from dispersants, defoamers, leveling agents, anti-settling agents, adhesion promoters, water scavengers, inorganic powders and inactive diluents,
[0019] b) adding a polyisocyanate as a second component in such an amount that the ratio of the number of isocyanate groups to the number of secondary amine groups of the first component is in the range from 0.9:1 to 1.5:1, preferably from 1:1 to 1.3:1,
[0020] c) optionally adding an inert diluent and / or an inorganic powder as a third component,
[0021] d) mixing all the components to obtain a homogeneous liquid,
[0022] e) Apply the mixed coating by a suitable method within its open time.
[0023] The present application also relates to an antistatic coating system, which comprises, from bottom to top, in the following order:
[0024] base(1),
[0025] Base coating (2),
[0026] a conductive layer (3), and
[0027] A top coating layer (4) is formed from the antistatic coating composition according to the present invention.
[0028] BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 : A schematic diagram of an antistatic coating system according to the present invention, wherein the reference numerals are listed as follows: 1 substrate; 2 primer layer; 3 conductive layer; and 4 top coating layer. DETAILED DESCRIPTION
[0030] definition
[0031] The terms "aspartic acid resin", "aspartic acid ester", "aspartic acid ester resin", "polyaspartic acid resin", "polyaspartic acid ester", and "polyaspartic acid ester resin" may be used interchangeably.
[0032] The term "aspartic acid ester having at least two secondary amine groups" is used for both Desmophen NH-types specified above and below. When it is mixed with a polyisocyanate and cured, it can be referred to as an "aspartic acid ester resin system".
[0033] The term "aliphatic polyisocyanate" is a curing agent for aspartic acid esters having at least two secondary amine groups (as written in the prior art).
[0034] Suitable aliphatic polyisocyanates are aliphatic diisocyanates, preferably 1,6-hexane diisocyanate (HDI), isophorone diisocyanate (IPDI), 4,4'-diisocyanatodicyclohexylmethane (H12MDI) or oligomers or derivatives of aliphatic diisocyanates, preferably biuret or isocyanurate or uretdione or iminooxadiazinedione or allophanate of HDI or isocyanurate of IPDI.
[0035] Particularly preferred aliphatic polyisocyanates are trimers of HDI, in particular isocyanurates of HDI. This results in aspartic acid ester resin systems having low viscosities, which are easy to apply.
[0036] The term “carbon nanotube” is a carbon tube whose diameter is in the nanometer range, in particular in the range from 1 nm to 50 nm, and whose wall is made of one or more layers of graphene, ie carbon with carbon atoms arranged in a ring.
[0037] Carbon nanotubes are industrially produced and commercially available in various qualities. They are electrically conductive. Single-walled carbon nanotubes, so-called "SWCNTs", are particularly suitable for the present invention. They all consist of carbon atoms, and their geometric structure can be considered to be a curled-up monolayer of graphene. They are preferably used as a dispersion in a liquid carrier material, in particular in a liquid that is highly compatible with the epoxy resin composition, in particular alkyl glycidyl ethers, fatty acid esters or ethoxylated alcohols.
[0038] The term "open time" refers to the period of time after mixing the components of a multi-component composition during which the mixed composition can be applied without defects. DETAILED DESCRIPTION OF THE INVENTION
[0040] In one embodiment, an antistatic coating composition according to the present invention is provided, comprising the following components:
[0041] Component A, one or more aspartic acid esters having at least two secondary amine groups, in an amount of 15% to 45% by weight, preferably 25% to 35% by weight, more preferably 30% to 35% by weight, based on the total amount of the composition:
[0042] Component B, carbon nanotubes, in an amount of 0.005 to 0.05 wt %, preferably 0.008 to 0.05 wt %, more preferably 0.01 to 0.02 wt %, based on the total amount of the composition; and
[0043] Component C: one or more other additives selected from dispersants, defoamers, leveling agents, anti-settling agents, adhesion promoters, water removers, inorganic powders and inactive diluents; and
[0044] Component D: at least one aliphatic polyisocyanate.
[0045] It has been found that if the amount of component B is too high, for example above 0.05 wt. %, preferably above 0.02 wt. %, the viscosity will be quite high, which results in the composition not being able to level out.
[0046] Preferably, the one or more aspartic acid esters having at least two secondary amine groups are selected from:
[0047] Component A1: an aspartic acid ester having two secondary amine groups and 250-280 NH equivalents, preferably 260-278 NH equivalents, most preferably 276 NH equivalents, and
[0048] Component A2: Aspartic acid ester having two secondary amine groups and 285-310 NH equivalents, preferably 288-300 NH equivalents, most preferably 290 NH equivalents.
[0049] Preferably, the viscosity of the aspartic acid ester resin in component A1 is 800-1100 mPa·s, preferably 900-1050 mPa·s, most preferably 1000 mPa·s.
[0050] Preferably, the viscosity of the aspartic acid ester resin in component A2 is 1000-1400 mPa·s, preferably 1100-1300 mPa·s, most preferably 1200 mPa·s.
[0051] Preferably, the aspartic acid ester resin in component A1 has the following structure:
[0052]
[0053] This aspartate ester can be prepared by the following scheme:
[0054]
[0055] Such aspartic acid esters are commercially available, e.g. NH 1420. It has a moderate reactivity towards aliphatic isocyanates, giving a gel time of about 1 hour.
[0056] Preferably, the aspartic acid ester resin in component A2 has the following structure:
[0057]
[0058] It was prepared by the following scheme:
[0059]
[0060] The prepared aspartic acid ester resin can be used as NH1520 / 7068 is commercially available, and the reactivity of the aspartic acid ester resin in component A1 is low, and its gel time is about 8 hours.
[0061] NH1420 is highly reactive to HDI drimer (Desmodur N3900, viscosity 630-830 mPa·s) and can be surface dried within 15 minutes. NH1520 has moderate reactivity towards HDI drimer. Therefore, it has been found that by NH1420 and NH1520 is combined to adjust the reaction rate to obtain an excellent solvent-free system with low viscosity. The film obtained in this way has excellent self-leveling and gloss, as well as excellent weather resistance, water resistance, solvent resistance, acid and alkali resistance and salt spray resistance. Generally, when the NCO content is low (for example, about 5%, the viscosity of the solvent-free system is 3000-5000mPa·s), the viscosity is not suitable for self-leveling.
[0062] The catalyst used above is a catalyst well known in the art, such as alkylates (such as Na salts), basic amines (such as tertiary amines), metal hydrides (such as NaH) and lithium amide (such as lithium diisopropylamide solution LDA).
[0063] Preferably, the carbon nanotubes are single-walled carbon nanotubes, e.g. 208's. 208's (208) is a dispersant for carbon nanotubes in ethylene oxide and a mono[(C12-14-alkoxy)methyl] derivative (CAS 68609-97-2 in SDS). 301's (301) is a dispersant for carbon nanotubes dispersed in alcohol and C12-15-branched and linear, ethoxylated propoxylated (CAS 120313-48-6 in SDS). When 208 and 301 are added to component A and / or component B in the same amount, 208 is able to achieve suitable antistatic properties, but the resistance of 301 exceeds 10 9 Ω, which fails in this application.
[0064] Preferably, the carbon nanotubes are dispersed in a liquid, preferably in a monoglycidyl ether of a C12-14-alcohol. More preferably, the carbon nanotubes have a composition of an alkyl glycidyl ether and an ammonium salt of a polyolefin-based derivative.
[0065] Preferably, the aliphatic polyisocyanate is a trimer of hexane-1,6-diisocyanate, preferably the isocyanurate of hexane-1,6-diisocyanate.
[0066] Preferably, the composition of the present invention does not contain a solvent, and the boiling point of the solvent at normal pressure is lower than 250°C.
[0067] Preferably, the dispersant may be a dispersant known in the art, for example 110 (phosphate copolymer with a certain acid value), 111 (a phosphate copolymer having a certain acid value in an inorganic solvent), 4010 (modified polyurethane with certain acid value and certain amine value) or 9250 (a copolymer having acid groups with a certain acid value) is commercially available.
[0068] Preferably, the defoaming agent may be one well known in the art, for example, 2723 (silicone-containing defoamer, 100% solid content), 900 (defoamer containing organomodified polysiloxane with fumed silica, 100% solids content), 1796 (defoamer containing defoaming polysiloxane with fumed silica, 100% solids content), 3268 (defoamer containing defoaming polysiloxane with fumed silica, 100% solids) or 1795 (organosilicone-free defoaming copolymer) is commercially available.
[0069] Preferably, the leveling agent may be a leveling agent well known in the art, for example, 327 (leveling agent containing polyether-modified methyl alkyl polysiloxane, 100% solid content), 354 (leveling agent containing polyacrylate, 100% solid content) or 361N (leveling agent containing acrylic copolymer, >98% solid content) is commercially available.
[0070] Preferably, the anti-settling agent may be an anti-settling agent known in the art, for example 7410T (liquid rheological agent containing modified urea, 40% solid content, solvent: amide ether) or 410 (liquid rheological agent containing modified urea, 52% solid content, solvent: N-methylpyrrolidone) was commercially available.
[0071] Preferably, the adhesion promoter may be an adhesion promoter known in the art, for example 303 (2-(3,4-exopycyclohexyl)ethyltrimethoxysilane), 403 (3-glycidyloxypropyltrimethoxysilane), 402 (3-glycidyloxypropylmethyldiethoxysilane) or 403 (3-glycidyloxypropyltriethoxysilane) is commercially available and its function is to increase the adhesion to the contact layer. If it is not used, the adhesion may be poor.
[0072] Preferably, the desiccant may be a desiccant known in the art, for example, a commercially available desiccant under 3A molecular sieve or 4A molecular sieve, and its function is to remove trace moisture from the substrate.
[0073] Preferably, the inorganic powder comprises 1250 mesh talc and / or 600 mesh silica powder 21.
[0074] Preferably, the inactive diluent may be an inactive diluent well known in the art, such as commercially available as Texanol or PMA, for adjusting viscosity and extending operating time.
[0075] Preferably, the antistatic coating composition according to the present invention further comprises environmentally friendly pigments, the heavy metal content of which cannot exceed the standard GB / T 22374-2018, for example, titanium dioxide.
[0076] In one embodiment, a method for preparing an antistatic coating composition according to the present application comprises the following steps:
[0077] a) preparing a first component by mixing in any order one or more aspartic acid esters, carbon nanotubes and one or more other additives selected from dispersants, defoamers, leveling agents, anti-settling agents, adhesion promoters, water scavengers, inorganic powders and inactive diluents,
[0078] b) adding a polyisocyanate as a second component in such an amount that the ratio of the number of isocyanate groups to the number of secondary amine groups of the first component is in the range from 0.9:1 to 1.5:1, preferably from 1:1 to 1.3:1,
[0079] c) optionally adding an inert diluent and / or an inorganic powder as a third component,
[0080] d) mixing all ingredients to obtain a homogeneous liquid, and
[0081] e) applying the mixed coating during its open time to form the antistatic composition.
[0082] In another embodiment, there is provided a method for preparing an antistatic coating composition according to the present invention, comprising the following steps:
[0083] a) preparing a pre-dispersed slurry by mixing at least one of component A, at least one of the carbon nanotubes in component B, at least one of the dispersants in component C, and at least one of the defoaming agents;
[0084] b) adding the pre-dispersed slurry to a mixture comprising at least one component A and at least one component C to form a main matrix;
[0085] c) optionally adding the primary matrix to a secondary matrix comprising at least one component A, a pigment and at least one component C to form an uncured antistatic coating composition;
[0086] d) adding a polyisocyanate as a curing agent in such an amount that the ratio of the number of isocyanate groups to the number of secondary amine groups is in the range of 0.9:1 to 1.5:1, preferably 1:1 to 1.3:1; and
[0087] e) applying the mixed coating to cure during its open time to form a cured antistatic coating composition.
[0088] It has been found that the preparation of the pre-dispersed slurry is very important. It facilitates uniform dispersion and a well-controlled addition of nanotubes, all of which ensure resistance stability.
[0089] Preferably, the secondary matrix is prepared by mixing at least one component A, a pigment and at least one of the components of component C, passing through a three-roll mill and grinding to achieve a fineness of less than 50 μm.
[0090] In the most preferred embodiment, in the antistatic coating composition of the present invention, the carbon nanotubes are 208; In the main matrix, the dispersant is 110; In the secondary matrix, if the pigment in the secondary matrix is titanium dioxide, the dispersant is 110; If the pigment in the secondary matrix is not titanium dioxide, the dispersant is 2013 one; the defoamer in both the primary matrix and the secondary matrix is 2723 0.5PHR and 32680.5PHR; The anti-settling agent in the primary matrix and the secondary matrix is 410; the dehydrating agents in the primary matrix and the secondary matrix are both 3A molecules; the adhesion promoters in the primary matrix and the secondary matrix are 403; The inactive diluent in the primary and secondary matrix is Texanol; these depend on the performance requirements.
[0091] When applied to form a coating, the best curing agents are N3600 (standard) or N3900 (hard). The weight ratio of the curing agent is 20wt%-25wt%, preferably 22wt%-24wt%, based on the total weight of the composition.
[0092] In another embodiment, an antistatic coating system is provided, comprising, from bottom to top, in the following order:
[0093] base(1),
[0094] Base coating (2),
[0095] a conductive layer (3), and
[0096] The top coating layer (4), which is formed from the antistatic coating composition according to the present invention, can be applied by roller coating or self-leveling coating.
[0097] Preferably, the top coating (4) has a thickness of about 10 6 to about 10 7 ohm range and a surface resistance of about 10 6 to about 10 7 Ground resistance in the ohm range.
[0098] In a most preferred embodiment, the coating system according to the present invention comprises:
[0099] The substrate (1) is also called a penetrating seal primer. It is composed of epoxy resin, such as Sikafloor-2500A and Sikafloor-2500B, wherein the weight ratio of Sikafloor-2500A: Sikafloor-2500B is 11.3:6. This epoxy resin is 0.1-0.2 kg / m 2 The amount of application;
[0100] The base coat (2) is also called a leveling layer. It consists of epoxy resin, curing agent and filler, such as Sikafloor-161A and Sikafloor-161LB, where the weight ratio of Sikafloor-161A: Sikafloor-161LB is 20.8:5.2. This system is applied at a rate of 0.8-1.2 kg / m 2 The amount of application;
[0101] A conductive layer (3), comprising:
[0102] Conductive medium: copper foil or ground point, and
[0103] Conductive primer, such as Sikafloor-220W A and Sikafloor-220W B, wherein the weight ratio of Sikafloor-220W A: Sikafloor-220W B = 4.98: 1.02. This layer has 1*10 3 -5*10 3 Ω resistance and 0.08-0.12kg / m 2 The amount of application;
[0104] A top coating layer (4) comprising:
[0105] The polyaspartic acid coating according to the invention:
[0106] Roller press* twice orange paint (0.3-0.5kg / m 2 ), or 0.5-0.7kg / m2 Scrape the self-leveling surface.
[0107] Compared with the prior art, the present invention has the following advantages:
[0108] 1. No irritating odor, low VOC in line with GB / T 22734-2018;
[0109] 2. Stable resistance performance, 10 6-7 Ω;
[0110] 3. Low viscosity and high solid content;
[0111] 4. Acid and alkali resistance, smooth surface and good stain resistance;
[0112] 5. Good compatibility, no obvious color difference, no flood and float;
[0113] 6. It can be made into self-leveling paint or orange paint; and
[0114] 7. Low temperature curing.
[0115] The following are examples of the present invention. These examples are illustrative only and are not intended to limit the scope of the present invention.
[0116] Example
[0117] Preparation Example:
[0118] The following trade names are effective and are commercially available from the market.
[0119] Preparation of carbon nanotube pre-dispersed slurry:
[0120] Will 1420 8.4 wt%, 1520 90 wt%, dispersant 0.3 wt%, defoamer 0.3 wt%, Matrix 208 (10 wt % single-walled carbon nanotubes in a liquid medium) 1 wt % was mixed and uniformly stirred at 2000-3000 rpm / hr to form a pre-dispersed slurry, which was labeled as Pre-CA.
[0121] This pre-dispersed slurry preparation is necessary because some carbon nanotubes are not easily dispersed in the matrix when added directly, so it needs to be made into a pre-slurry first.
[0122] Preparation of Matrix A1 (Main Matrix):
[0123] Pre-CA 15.8 wt%, 1520 25.2 wt%, dispersant 0.4 wt%, defoamer 1.0 wt%, leveling agent 0.5 wt%, anti-settling agent 0.2 wt%, adhesion promoter 0.5 wt%, dehydrating agent 6 wt%, 1250 mesh talc 24.4 wt%, 600 mesh silica powder 21 wt%, inactive diluent 5 wt% are mixed and uniformly stirred at 600-1000 rpm / 30 minutes to form matrix A1.
[0124] Preparation of Matrix A3 (Main Matrix):
[0125] Pre-CA 21% by weight 1520 19 wt %, dispersant 0.4 wt %, defoamer 1.0 wt %, leveling agent 0.5, anti-settling agent 0.2 wt %, adhesion promoter 0.5 wt %, dehydrating agent 6 wt %, 1250 mesh talc 24.4 wt %, 600 mesh silica powder 21, inactive diluent 5 wt % are mixed and uniformly stirred at 600-1000 rpm / 30 minutes to form matrix A3.
[0126] Preparation of Matrix A2 (Secondary Matrix):
[0127] Will 1520 41 wt%, dispersant 0.4 wt%, defoamer 1.0 wt%, leveling agent 0.5, anti-settling agent 0.2 wt%, adhesion promoter 0.5 wt%, dehydrating agent 6 wt%, 1250 mesh talc 14.4 wt%, pigment 10 wt%, 600 mesh silica powder 21 wt%, inactive diluent 5 wt% were mixed and uniformly stirred at 600-1000 / 30 minutes to form matrix A2. Matrix A2 was then passed through a three-roll mill and ground to obtain a fineness of less than 50 μm.
[0128] In matrix A2, if the pigment is titanium dioxide, the dispersant is 110. 111. 4010 or 9250; if the pigment is not titanium dioxide, the dispersant is 163. 161. 2013, One of 2152.
[0129] Preparation of the first component F-1:
[0130] 95 parts by weight (ppw) of Base A3 were mixed with 5 ppw of Base A2 to form a first component F-1.
[0131] Preparation of the first component F-2:
[0132] 95 parts by weight (ppw) of Base A1 were mixed with 5 ppw of Base A2 to form a first component F-2.
[0133] The second component S-1:
[0134] Using an isocyanate content of about 23% by weight N 3600 (aliphatic polyisocyanate) was used as the second component S-1.
[0135] Example:
[0136] All resistance tests were performed according to the well-known standard GB / T 22374-2018 in the field, including:
[0137] 1. Test conditions: Ambient temperature 20-25℃, relative humidity (RH) 40-60%; the surface of the test sample should be clean and not contaminated by impurities. The surface should not be cleaned with solvents. At the same time, the test electrode should be clean and free of wet media adhesion.
[0138] 2. Test instrument: Metriso-3000 (10 4 -10 6 Using the 10V range, 10 6 -10 9 Use 100V range)
[0139] Table I
[0140]
[0141]
[0142] 1): d = day;
[0143] 2): Rs = surface resistance;
[0144] 3):Re = ground resistance / volume resistance.
[0145] Table II
[0146]
[0147]
[0148] 1): d = day;
[0149] 2): Rs = surface resistance;
[0150] 3):Re = ground resistance / volume resistance.
[0151] Table III
[0152]
[0153]
[0154]
[0155] 1): d = day;
[0156] 2): Rs = surface resistance;
[0157] 3):Re = ground resistance / volume resistance.
[0158] Table IV
[0159]
[0160]
[0161] 1): d = day;
[0162] 2): Rs = surface resistance;
[0163] 3):Re = ground resistance / volume resistance.
[0164] Other test results measured by methods well known in the art:
[0165] Solid content ≥95%, acid resistance 10%H 2 SO 4 Passed, alkali resistance 20% NaOH passed, water resistance 168h passed, adhesion ≥2.0MPa, abrasion resistance <50mg, roller coating pencil hardness 1h-2h (48h).
Claims
1. An antistatic coating composition, characterized in that: It contains the following components: Component A, one or more aspartic acid esters having at least two secondary amine groups, in an amount of 10 to 40 wt % based on the total amount of the composition; Component B, one or more carbon nanotubes, in an amount of 0.005 wt % to 0.05 wt % based on the total amount of the composition; and Component C: one or more other additives selected from dispersants, defoamers, leveling agents, anti-settling agents, adhesion promoters, water removers, inorganic powders and inactive diluents; and Component D: at least one aliphatic polyisocyanate as curing agent.
2. The antistatic coating composition according to claim 1, wherein the one or more aspartic acid esters having at least two secondary amine groups are selected from: Component A1: an aspartic acid ester having two secondary amine groups and 250-280 NH equivalents, preferably 260-278 NH equivalents, most preferably 276 NH equivalents, and Component A2: Aspartic acid ester having two secondary amine groups and 285-310 NH equivalents, preferably 288-300 NH equivalents, most preferably 290 NH equivalents.
3. The antistatic coating composition according to claim 2, wherein the viscosity of the aspartic acid ester resin in component A1 is 800-1100 mPa·s, preferably 900-1050 mPa·s, most preferably 1000 mPa·s.
4. The antistatic coating composition according to claim 2, wherein the viscosity of the aspartic acid ester resin in component A2 is 1000-1400 mPa·s, preferably 1100-1300 mPa·s, most preferably 1200 mPa·s.
5. The antistatic coating composition according to claim 2, wherein the aspartic acid ester resin in component A1 has the following structure:
6. The antistatic coating composition according to claim 2, wherein the aspartic acid ester resin in component A2 has the following structure:
7. The antistatic coating composition according to claim 1, wherein the carbon nanotubes are single-walled carbon nanotubes.
8. The antistatic coating composition according to claim 1, wherein the carbon nanotubes are dispersed in a liquid, preferably in a monoglycidyl ether of a C12-14-alcohol.
9. The antistatic coating composition according to claim 1, wherein the aliphatic polyisocyanate is a trimer of hexane-1,6-diisocyanate, preferably an isocyanurate of hexane-1,6-diisocyanate.
10. The antistatic coating composition according to any one of claims 1 to 9, wherein the composition is free of solvent.
11. A method for preparing an antistatic coating composition according to any one of claims 1 to 10, comprising the following steps: a) preparing a first component by mixing in any order one or more aspartic acid esters, carbon nanotubes and one or more other additives selected from dispersants, defoamers, leveling agents, anti-settling agents, adhesion promoters, water scavengers, inorganic powders and inactive diluents, b) adding a polyisocyanate as a second component in such an amount that the ratio of the number of isocyanate groups to the number of secondary amine groups of the first component is in the range from 0.9:1 to 1.5:1, preferably from 1:1 to 1.3:1, c) optionally adding an inert diluent and / or an inorganic powder as a third component, d) mixing all ingredients to obtain a homogeneous liquid, and e) Apply the mixed coating within its open time.
12. An antistatic coating system, characterized in that: Contains the following order from bottom to top: base(1), Base coating (2), a conductive layer (3), and A top coating layer (4) formed from the antistatic coating composition according to any one of claims 1 to 10.
13. The antistatic coating system of claim 12, wherein the surface resistance of the top coating (4) is about 10 6 - Approx. 10 7 Ohms, the ground resistance is about 10 6 - Approx. 10 7 ohm.
Citation Information
Patent Citations
Polyurea anti-static elastic self-leveling floor coating and preparation method thereof
CN106675485A
Aspartic ester self-leveling coating and preparation method thereof
CN106867377A
Cited By
Anti-yellowing asparagine polyurea plastic runway surface layer material and preparation method thereof
CN121064717A